99.5k views
4 votes
Solve for s. -5(2s + 5) = -3s + 4

Solve for s. -5(2s + 5) = -3s + 4-example-1
User MBrizzle
by
5.9k points

2 Answers

0 votes

Answer:

s=-2

Explanation:

-5(2s+2)=-3s+4

-10s-10=-3s+4

-10=-3s+4+10s

-10=7s+4

-10-4=7s

-14=7s

-14/7=s

-2=s

s=-2

User Faris Tangastani
by
4.8k points
4 votes

Answer:

The answer is -2. Good luck!

User Pierre Lapointe
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.